The Spiral of Violence: A Critical Analysis of The Genealogy of Islamophobia - Imam, Mohammad Fuyudun Niam; Samudra, Fawes; Solahudin, Muhammad (Yayasan Pesantren Mahasiswa An-Nur, 2023)
The rise of terrorism by extremist groups with religious backgrounds and the development of Islamophobia in the West after 9/11 are essential issues that need to be addressed. After the WTC incident in 2001, the US declared a